Faktor-Faktor Yang Mempengaruhi Minat Umkm Menjadi Nasabah Bank Syariah Indonesia Di Kota Kupang - Marianus Adi Nahak; Fransina W. Ballo; Maria Indryani Hewe Tiwu (Journal of Islamic Economics and Finance, 2024)
This research aims to find out whether trust, service and return of results influence MSMEs' interest in becoming Sharia Bank customers. This research uses a quantitative approach by obtaining primary data from questionnaires by taking samples using a random sampling technique with the selection of the entire population in this study being sampled using the census method or saturated sample. Data collection techniques were carried out using observation, interviews, questionnaires and documentation. The data processing technique used is multiple regression data analysis using SPSS 25, UI hypothesis testing, validity testing, and classical assumption testing. This research shows that trust, service and returns have a significant effect on MSMEs' interest in saving at Sharia Banks.